(untitled) (Journal of EAHIL, 2024)
Medical Libraries have become central in evidence synthesis conduct – an evolving field. The Medical Library at Charité initiated Systematic/Scoping Reviews, an eight-part workshop series designed to provide comprehensive education and guidance on systematic and scoping review methods. Each session covers a specific step of the review process and offers participants who are conducting a review active engagement in these methodological steps using their own review question. This article provides a summary of each workshop session, outlining preparation requirements, workshop content, and challenges faced by both learners and the teaching team. The course has been well received by participants and has proven to be a valuable complement to the other health information literacy trainings offered by the Medical Library.